Geschlechtsdiskriminierende Wirtschaftswerbung : zur Rechtmäßigkeit eines Verbots geschlechtsdiskriminierender Werbung im UWG - Völzmann, Berit (Schriften zur Gleichstellung der Frau, 2014)
Since the 1970s sexism in advertising has been the subject of many political and social discourses as well as the reason for social-scientific research. For the first time, the problem is analysed thoroughly in its legal dimensions. Based on social-scientific research and a critical analysis of the efficiency of the German Advertising Standards Authority the examination of the German constitutional law reveals in which regards gender-discriminating advertising violates constitutional rights and to what extent a legal prohibition of such advertising would be justified. Following a subsumption under European law the author analyses if the German UWG (Act Against Unfair Competition) is a possible instrument of regulation to ensure protection against gender discriminating advertising. The author substantiates that the UWG is to be interpreted value-related and assigns the constitutional assessments to the unfair competition law. The thesis concludes with a suggestion for a norm that contains the prohibition of gender-discriminating advertising to be implemented in the UWG.